A flame in the North - Saintcrow, Lilith (Black Land's Bane, 2024)
"The Black Land is spent myth. Centuries have passed since the Great Enemy was slain. Yet old fears linger, and on the longest night of the year, every village still lights a ritual fire to banish the dark. That is Solveig's duty. Favored by the gods with powerful magic, Sol calls forth flame to keep her home safe. But when her brother accidentally kills a northern lord's son, she is sent away as weregild--part hostage, part guest--for a year and a day. The further north Sol travels, the clearer it becomes the Black Land is no myth. The forests teem with foul beasts. Her travel companions are not what they seem, and their plans for her and her magic are shrouded in secrecy. With only her loyal shieldmaiden and her own wits to reply upon, Sol must master power beyond her imagination to wrest control of her fate. For the Black Land's army stirs, ready to cover the world in darkness--unless Sol can find the courage to stop it"--